KADAR HAMBAT MINIMUM (KHM) DAN KADAR BUNUH MINIMUM (KBM) EKSTRAK BIJI PEPAYA (Carica papaya L) TERHADAP BAKTERI Streptococcus mitis - subekti, stella; Molek, Molek; Sim, Mellisa (Prima Journal of Oral and Dental Sciences, 2019)
One of the potential herbs that can be used as a medicine in dentistry is young papaya seed (Carica papaya L.). Papaya seed contains active component as antibacterial such as flavonoid, alkaloid, triterpenoid, and tanin that can inhibits gram-positive and gram-negative bacteria. Objective: The purpose of this research is to examine the effectivity of Young Papaya seed (Carica papaya L.) at inhibiting the growth of Streptococcus mitis. Material and Method: This research uses the experimental laboratory. Inhibition test using the dilution method with young papaya seed extract as the test material.The concentration of the young papaya seed extract in this research is 0,5%, 1%, 2%, 3%, and 4%. Determination of the KHM result can views of turbidity from test tube, after that subculture to the blood agar dish to see the KBM result. Result: The result shows that at 0,5% concentrate the average value is 1000±0. At 1% concentrate the average value is 927,5±5,260. Concentrate 2% the average value is 452,75±10,813. Concentrate 3% the average value is 213,75±2,986. At 4% concentrare the average value is 0±0. Conclusion: At 1%, concentrate is the KHM inhibiting and 4% concentrate is the KBM inhibiting. Young papaya seed extract is effective at inhibiting the growth of Streptococcus mitis.